COSMIC REIONIZATION ON COMPUTERS. I. DESIGN AND CALIBRATION OF SIMULATIONS - Gnedin, Nickolay Y (The Astrophysical journal, 2014)
Cosmic Reionization On Computers is a long-term program of numerical simulations of cosmic reionization. Its goal is to model fully self-consistently (albeit not necessarily from the first principles) all relevant physics, from radiative transfer to gas dynamics and star formation, in simulation volumes of up to 100 comoving Mpc, and with spatial resolution approaching 100 pc in physical units. In this method paper, we describe our numerical method, the design of simulations, and the calibration of numerical parameters. Using several sets (ensembles) of simulations in 20/ h super(-1) Mpc and 40 h super(-1) Mpc boxes with spatial resolution reaching 125 pc at z = 6, we are able to match the observed galaxy UV luminosity functions at all redshifts between 6 and 10, as well as obtain reasonable agreement with the observational measurements of the Gunn-Peterson optical depth at z < 6.